Comparison of manual versus mechanical cervical anastomosis in a prospective series of patients with esophagectomy due to cancer - Castaño Llano, Rodrigo (2021)
Objectives: The scarce existing literature suggests having a lower rate of anastomotic leakage and less late stricture formation after stapled esophagogastric anastomosis compared to the manual anastomosis technique. The aim of the present study is to compare the surgical outcomes of termino-lateral manual cervical anastomosis versus mechanical anastomosis by later lateral stapling, after transhiatal esophagectomy for cancer. Materials and methods: A retrospective review of patients undergoing transhiatal esophagectomy with manual or mechanical anastomosis for neoplasia was performed at three institutions in Medellin, between 2011 and 2018. Endpoints included leak rate, morbidity, mortality, hospital stay, and endoscopically identified anastomotic strictures requiring dilatation. Results: 68 patients (40 men, 59%) were evaluated, 37 with manual anastomosis and 31 with mechanical anastomosis with similar demographic characteristics. Anastomotic leaks occurred in 13 patients (19.1%), with no difference found between manual and mechanical anastomosis (18.9 vs. 19.3%; p=0.93). Overall morbidity (61%), in-hospital mortality (3%) and length of hospital stay (median 12 days) were not affected by anastomotic technique. Follow-up endoscopic evaluation was available in all patients and anastomotic stricture associated or not with leak was detected in 18 patients (22%), in cases of stricture without leak is more frequent with manual than mechanical anastomosis technique (21.6 vs 6.4%; p=0.07) with longer duration of surgical procedure in case of manual anastomosis (p=0.05). Conclusions: Our non-randomized study suggests that the manual anastomosis technique results in a shorter surgical time and a lower stricture rate than mechanical anastomosis in cervical esophagogastric reconstruction after transhiatal esophagectomy, with a similar rate of leakage, hospital stay and morbidity and mortality.